PARTICLES SIZE AND LATTICE STRAIN EFFECT ON THE OPTICAL CONSTANTS OF Fe3O4 NANOPARTICLES - Indrayana, I Putu Tedy; Tuny, Margaretha Tabita (Universitas Mataram, 2021)
In the case of optical sensors such as the Surface Plasmon Resonance (SPR) sensor, the Fe3O4 nanoparticles play a role to boost the signal however they can increase the detection sensitivity of the biosensor. For this application, the optical properties of Fe3O4 nanoparticles need to be studied. The optical properties are described in terms of their optical constants. Therefore, this work was purposed to study the effect of the particle size and lattice strain on the optical constants of Fe3O4 nanoparticles. Samples were synthesized by using the coprecipitation technique. Two calcination temperatures, i.e., 150oC and 250oC for 4 hours were applied to the samples. Samples were characterized for their diffraction pattern and optical properties by using XRD and Specular UV-Vis Spectroscopy technique, consecutively. The particle size and lattice strain were estimated by using the Williamson-Hall (W-H) method. The effect of the particle size and their optical constants on the reflectance curve in the SPR sensor application was also performed toward a simulation by using Winspall 3.02 software. The results show that calcination temperature causes an increase in particle size and a decrease in lattice strain. The optical constants, such as absorbance (A), absorption coefficient (Î±), extinction coefficient (k), refractive index (n), dielectric constants (Îµ), optical conductivity (Ïƒ), and the Urbach energy (Eu) significantly depended on particles size and lattice strain. However, the particle size and optical constant were significantly influent the SPR angle in the reflectance curve of Fe3O4